INTEGRASI STUDI NASKAH ARAB KE DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI - Firman; Muzaat, Syahid Bin (Pascasarjana IAIN Sorong, 2025)
This study analyzes the urgency and strategies for integrating Arabic manuscript studies into the Islamic Religious Education curriculum at Indonesian universities. Using a qualitative approach and descriptive analysis, this study examines the implementation of Arabic manuscript studies as an integral part of Islamic Religious Education (PAI) learning. The results indicate that integrating Arabic manuscript studies can improve the quality of Islamic Religious Education (PAI) learning by developing critical analysis skills, contextual understanding of Islamic sources, and preserving Islamic intellectual heritage. The main challenges faced include limited human resources, accessibility of manuscripts, and integration of digital technology. This study recommends the development of an integrated curriculum, increasing the capacity of lecturers, and utilizing digital technology to support effective learning.